2014
DOI: 10.1130/g35092.1
|View full text |Cite
|
Sign up to set email alerts
|

Increased channelization of subglacial drainage during deglaciation of the Laurentide Ice Sheet

Abstract: The confi guration of subglacial meltwater is a critical control on ice sheet dynamics, and the presence of pressurized water distributed across the bed can induce dynamic instabilities. However, this process can be offset by effi cient evacuation of water within large subglacial channels, and drainage systems beneath alpine glaciers have been shown to become increasingly channelized throughout the melt season in response to the increased production of meltwater. This seasonal evolution has recently been infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 28 publications
7
66
0
Order By: Relevance
“…At its maximum, approximately 27% of the LIS margin was streaming, but this value decreased to between 25% and 20% from 16 ka to 13 ka, and then rapidly dropped to ~5% at 11 ka (Stokes et al, 2016). This implies that the final 4 to 5 ka of deglaciation was largely driven by surface melt, which is corroborated surface mass balance modelling (see Section 4.1) and inferences based on the density of subglacial meltwater conduits (eskers) (Storrar et al, 2014). Stokes et al (2016) also used a simple scaling relationship based on the width and discharge of modern ice streams to estimate the potential cumulative discharge from Laurentide ice streams through time, and found that this decreased and was strongly scaled to the ice sheet's volume.…”
Section: Reprinted By Permission From Macmillansupporting
confidence: 69%
“…At its maximum, approximately 27% of the LIS margin was streaming, but this value decreased to between 25% and 20% from 16 ka to 13 ka, and then rapidly dropped to ~5% at 11 ka (Stokes et al, 2016). This implies that the final 4 to 5 ka of deglaciation was largely driven by surface melt, which is corroborated surface mass balance modelling (see Section 4.1) and inferences based on the density of subglacial meltwater conduits (eskers) (Storrar et al, 2014). Stokes et al (2016) also used a simple scaling relationship based on the width and discharge of modern ice streams to estimate the potential cumulative discharge from Laurentide ice streams through time, and found that this decreased and was strongly scaled to the ice sheet's volume.…”
Section: Reprinted By Permission From Macmillansupporting
confidence: 69%
“…This broad pattern is also seen in the FIS (Boulton et al, 2009) and, while eskers can clearly form over softer sedimentary beds, they are typically less common and depict a more chaotic and fragmentary pattern (Shilts et al, 1987;Storrar et al, 2014a). More recently, Storrar et al (2014b) showed that the number of eskers increased during deglaciation of the LIS across the Canadian Shield, coinciding with increased rates of ice margin retreat during climatic warming. This is reminiscent of the seasonal evolution of drainage systems in much smaller valley glaciers (Hubbard and Nienow, 1997) and implies that drainage systems (and therefore subglacial lubrication) evolve over millennial time-scales.…”
Section: Subglacial Hydrology Of Ice Sheets and Subglacial Lakesmentioning
confidence: 90%
“…Discrete, channelized drainage systems developed in association with streamlined terrain, whereas eskers more frequently formed in areas for which ice streaming has not been reconstructed (Storrar et al 2014;Margold et al 2015;Greenwood et al 2016).…”
Section: Late Wisconsinan Glacial Historymentioning
confidence: 99%
“…5B-5E, 11B-11J) are evidence of the transition from rapid ice-flow conditions and formation of drumlinized terrain in the subglacial zone to terrain produced by debris melt-out from stagnant, heavily crevassed ice masses in the ice-marginal zone (cf. Eyles and Eyles 1992;Clark and Walder 1994;Brennand and Shaw 1994;Harper et al 1998;Boulton et al 2001;Cutler et al 2002;Clark et al 2004;Fisher et al 2005;Jørgensen and Sandersen 2006;Boulton et al 2009;Burke et al 2012;Kehew et al 2012;Perkins et al 2013;Storrar et al 2014;Margold et al 2015;Greenwood et al 2016). Subglacial channels and eskers running upslope over clay-rich basal till plains and bedrock terrain imply phreatic meltwater flow under recessional ice masses.…”
Section: Laurentide Subglacial Meltwater Drainage Terrainsmentioning
confidence: 99%